The Effect of Low Dietary Vitamin K Intake on the Development of Osteoarthritis in Aging Mice. (29th May 2020) - Shea, M Kyla; Harshman, Stephanie; Booth, Sarah; Smith, Donald; Carlson, Cathy; Harper, Lindsey; Cancela, Leonor; Simão, Marcio; Loeser, Richard
Abstract: Objectives: Epidemiological evidence suggests that low vitamin K status is associated with osteoarthritis (OA) development and progression. However, it is not clear if low vitamin K intake is causally linked to OA. To address this gap, we manipulated vitamin K intake in aging mice to test its effect on OA development. Methods: Eleven-month old male C57BL/6J mice were randomly assigned to a low phylloquinone diet containing 120 mcg phylloquinone/kg diet (n = 32) or a control diet containing 1.5 mg phylloquinone/kg diet (n = 30) for 6 months. Knee OA was evaluated histologically using Safranin O and H&E staining. Adjacent sections were immunostained using antibodies directed against matrix gla protein (MGP) and gla rich protein (GRP), two vitamin K-dependent proteins present in cartilage that are implicated in OA. Post-mortem phylloquinone concentrations in liver, kidney, intestine, and brain were measured using HPLC. Results: While body weight gain was comparable between the two groups (repeated measures ANOVA, group P = 0.63, group*time P = 0.77, time P < 0.01), mortality was increased in the low phylloquinone diet group compared to the control group (eleven versus three mice) within the first 100 days of the experiment (log-rank test P = 0.02). The phylloquinone tissue concentrations were lower in the mice fed the low vitamin K diet compared to those fed the control diet (Wilcoxon test, all P < 0.01). Mice fed the low phylloquinone diet had higher Safranin-O scores (indicative of articular cartilage proteoglycan loss) compared to mice fed the control diet [median (interquartile range) = 20 (11) and 14 (14), respectively; Wilcoxon two sample test P = 0.01]. The articular cartilage structure scores did not differ between the two groups [median (interquartile range) = 11 (11) and 9 (9), respectively; Wilcoxon test P = 0.19]. While MGP and GRP were expressed in articular and meniscal cartilage, expression did not differ significantly between the two groups (Wilcoxon P ≥ 0.24). Conclusions: Our findings suggest low vitamin K status can promote articular cartilage proteoglycan loss in older male mice. Future studies are needed to confirm our findings and obtain a better understanding of the molecular mechanisms underlying vitamin K's role in OA. Funding Sources: The National Institute of Arthritis, Musculoskeletal and Skin Disease and the US Department of Agriculture.